Pharmacists’ perceptions of the new pharmaceutical vaccination service in Romania: a comprehensive first two-years evaluation - Buicu, Corneliu-Florin; Naidin, Mihaela-Simona; Chereches, Marius Calin; Dimulescu, Marina-Daniela; Turcu-Stiolica, Adina (Frontiers in Pharmacology, 2025)
IntroductionPharmacy-based vaccination services are now available in 56 countries, including Romania, that started administering the flu-vaccines in the community pharmacies from 2022. Assessing how pharmacists managed this new pharmaceutical service in Romania is the subject of this study.MethodsA cross-sectional study was conducted among all the pharmacies from Romania that were authorized to provide this service (442 pharmacies, from which 53 were in rural areas). An online survey was created using Google Forms and included 28 items, with 24 closed-ended questions and 4 open-ended questions. The questionnaire covered six sections: General information, Patient perspective, Authorization and training within the pharmacy, Administration of flu vaccine services, Pharmacy logistics, and Staff satisfaction. Descriptive statistics and chi-squared tests were applied.ResultsIn total, 180 pharmacists participated (response rate was 41%), and the respondents were the pharmacists who administered flu vaccines in these pharmacies. Among the respondents, 92.8% were from urban community pharmacies, and most of them were from Bucharest (26.1%) and East Romania. 88% of respondents considered that this new service will significantly impact the future increase in vaccine coverage rates in Romania. Regarding patients’ perception of this pharmaceutical service (provided by pharmacists), the vaccination service was evaluated very positively by 63% patients and positively by 18% patients, with statistically different perceptions between the types of the pharmacies (p < 0.01). A very positive vaccination evaluation was observed more often among national chain pharmacies (73.1%) rather than among local chain pharmacies (35.9%) or independent pharmacies (36.4%). Regarding logistical barriers, 39% of pharmacies reported no issues with vaccine supply. Moreover, 97% of pharmacies had adequate protective materials to safely administer vaccines. In terms of overall satisfaction, 23% of pharmacists reported being very satisfied, while 39% indicated they were satisfied with the new pharmaceutical service they were providing. The majority (82%) felt that their salaries should be increased related to the vaccination service. Additionally, there is a need for improvements in the pharmacy schedule and the advance scheduling of vaccinations.ConclusionThis study was developed to assist future health policies through expansion of advanced pharmaceutical services, and adding other vaccines to community pharmacy portfolios.